Visual Strategies in Video Branding to Build a Professional Image: A Case Study of the Video “Pruways” - Firdaus Tara Putra; Pratama Bayu Widagdo (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
In a competitive digital era, video has become an important strategy in brand communication to build a professional image. This study analyzes the internal video